Comparative transcriptomic analysis of Illumina and MGI next-generation sequencing platforms using RUNX3- and ZBTB46-instructed embryonic stem cells - Póliska, Szilárd; Fareh, Chahra; Lengyel, Adél; Göczi, Loránd; Tőzsér, József; Szatmari, Istvan (Frontiers in Genetics, 2024)
We have previously observed phenotypic and developmental changes upon the ectopic expression of the RUNX3 or the ZBTB46 transcription factors in mouse embryonic stem cell (ESC) derived progenitors. In this study we evaluated the gene expression profiles of the RUNX3-and the ZBTB46-instructed murine ESCs with RNA-seq testing two next generation sequencing (NGS) technologies.We compared the DNA nanoball (DNB) based DNBSEQ G400 sequencer (MGI) with the bridge-PCR based NextSeq 500 instrument (Illumina) for RNA sequencing. Moreover, we also compared two types of MGI sequencing reagents (Standard-versus Hot-MPS) with the DNBSEQ G400.We observed that both sequencing platforms showed comparable levels of quality, sequencing uniformity, and gene expression profiles. For example, a highly overlapping RUNX3 and ZBTB46 regulated gene lists were obtained from both sequencing data sets. Moreover, we observed that the Standard and the Hot-MPS derived RUNX3 and ZBTB46 regulated gene lists were also considerably overlapped. This transcriptome analysis also helped us to identify differently expressed genes in the presence of the transgenic RUNX3 or ZBTB46. For example, we found that Gzmb, Gzmd, Gzme, Gdf6 and Ccr7 genes were robustly upregulated upon the forced expression of Runx3, on the other hand, Gpx2, Tdpoz4 and Arg2 were induced alongside the ectopic expression of Zbtb46.Discussion: Similar gene expression profile and greatly overlapping RUNX3 and ZBTB46 regulated gene sets were detected with both DNA sequencing platforms. Our analyses demonstrate that both sequencing technologies are suitable for transcriptome profiling and target gene selection. These findings suggest that DNBSEQ G400 represents a cost effective alternative sequencing platform for 2 This is a provisional file, not the final typeset article gene expression monitoring. Moreover, this analysis provides a resource for exploration of the RUNX3-and ZBTB46-dependent gene regulatory networks.